MicroRNA-mediated regulation of ferroptosis via GPX4: mechanisms and therapeutic opportunities - S Satvika; B Nivedhitha; K Mounish; B Prathamesh; K L Milan; K. M. Ramkumar (Molecular Biology Reports, 2026)

Identification and validation of PANX1 as an inflammasome-related biomarker in gestational diabetes mellitus: insights from machine learning and experimental approaches - Padmanaban M. Abirami; K. L. Milan; M. Anuradha; Kunka Mohanram Ramkumar (Mammalian Genome, 2026)

Formulation and Evaluation of a Flutrimazole-Loaded Microemulsion for Enhanced Topical Delivery and Antifungal Efficacy - Shivani Singh; Ramkumar Chaudhary (Journal of Pharmaceutical Innovation, 2026)

Source, dynamic, and environmental impact of microplastic in aquatic ecosystem: A review - N. Radha; G. Sreelal; Sakthivel Murugan; S. Ramkumar; Balamurugan Paneerselvam (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Photocatalytic and antifouling performance of g-C3N4, CeO2, and ZnO-grafted PVDF/TiO2 nanohybrid membranes: a comparative study - S. Nivedita; M. Induja; Mani Durai; Karthikeyan Manivannan; Vinoth Kumar Raja; Nagaraj Murugan; Dharani Shanmugapriya; Vijayakumar Paranthaman; Amanullah Fatehmulla; Ramkumar Vanaraj; Paskalis Sahaya Murphin Kumar (Environmental Geochemistry and Health, 2026)

Asymptotic properties of count models for automobile insurance claims in emerging markets: Insight from Tanzania - Laurent L. Lulu; Ramkumar T. Balan; Peter Josephat Kirigiti (Next Research, 2026)

Influences of rainfall, river discharge and land use on groundwater quality in the Cauvery River Delta, southern India: Implications on agricultural production and sustainability - Karuppusamy Balasubramani; Deepthi Nanjappa; Paramasivan Ramesharavind; Kanagaraj Madhan Raj; Muthuvairavasamy Ramkumar; Ramasamy Nagarajan; Praveen Balabaskaran Nina (CATENA, 2026)

Gamma-linolenic acid production in Sesamum indicum (L.) using Δ6Desaturase gene from microalgae Isochrysis sp - Ramkumar Muthu; Jeyakumar Balakrishnan; Parthasarathy Ayothi; Kathiresan Shanmugam (Journal of Plant Biochemistry and Biotechnology, 2026)

Airglow imager observation of equatorial-plasma-irregularities in the Indian low/sub-low latitudes getting pinched-off and mergers during after/before midnights - T.K. Ramkumar; M.G. Keerthana; G.K. Prashant; Suparba Goswami; Keerthana Ramesh; Shravani Ahire (Advances in Space Research, 2026)

Advancing sustainable seaweed production: linking technology, policy, and ecology for a resilient blue economy - Saravanan Ramachandran; Pranaveeka Rajasekaran; Manasa Ramkumar; Puluputturi Nithin Reddy; Dasari Vishal; Sriharish Rajan; Namitha Madhu; Srividya Manikandan; Niranjan Krishnan; Sabarinath Sankarannair (Environmental Science and Pollution Research, 2026)

A Review on the Biodegradation of Kraft Lignin Wastes to Minimize Pollution Load in Paper Industry - Shrinidhi Sureshbabu; Ashmitha Kalairaj; Swethashree Rajendran; V. Ramkumar; Rames C. Panda; T. Senthilvelan (Water, Air, & Soil Pollution, 2026)

Gene silencing strategy for fall armyworm (Spodoptera frugiperda) control utilizing dsRNA targeting vATPase - Ranganathan Muthusamy; Govindaraju Ramkumar; Sengottayan Senthil-Nathan; Narayanasamy Prabhu; Naraayanan Madhiyalagan (Phytoparasitica, 2026)

Mechanistic and AI-assisted evaluation of paclitaxel-loaded HSPC liposomes for targeted breast cancer therapy - Vikram Subraya Shenoy; Prashant Nayak; Ramkumar Pillappan; Shrinivas R. Zanwar; Yogesh H. Bhosale; Devendra L. Bhuyar; Mukesh Chandra Sharma; Sunil Tulshiram Hajare (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Decoding PANoptosis: Crosstalk of cell death pathways in immunity and inflammation - K. Subashree; Kannan Harithpriya; Goutham V Ganesh; Kunka Mohanram Ramkumar (Immunologic Research, 2026)

Modulating IL-1β-induced pro-atherogenic endothelial responses through drug repurposing - Kundan Solanki; Sk Rameej Raja; Sunanda Samanta; P. S. Shishira; Anjali Roy; Parimal Kar; Swati Biswas; K. M. Ramkumar; Mirza S. Baig (Inflammopharmacology, 2026)

Machine learning-enhanced QSAR modeling for predicting drug efficacy against the RET V804M kinase domain mutation - Bithia R; Durga Shree Nagabushanam; Ramkumar Thirunavukarasu; George Priya Doss C (Molecular Diversity, 2026)

Emissions and health risks of prolonged incense burning in worship spaces: simulated real-life scenarios and strategic approaches for exposure assessment, control, and mitigation - Gopal Ashok Gupta; Roshan Kumar Singh; Janakarajan Ramkumar; Sandip Patil; Tarun Gupta (Air Quality, Atmosphere & Health, 2026)

Tectono-climatic controls on episodic paleosurface development in the Cauvery Basin, Southern India: Implications for basin-scale landscape dynamics - AL Fathima; M. Ramkumar; K. Balasubramani; P.D. Roy; Pankaj Kumar; R. Nagarajan; S. Rajveer (Rhizosphere, 2026)

Spatiotemporal patterns of jellyfish distribution along the Maharashtra coast, India - M.R. Ashpel Mano; S. Ramkumar; Asha T. Landge; S. Abuthagir Iburahim; K. Nikhil; Sonam Angmo; Karankumar Ramteke; B.B. Nayak; Suryapraba (Regional Studies in Marine Science, 2026)

First record of Cassiopea xamachana ephyrae from the wild in India, with insights into its life history and development - L. Ranjith; Raju Saravanan; K.S. Sobhana; I. Jagadis; S. Ramkumar; C. Kalidas; D. Linga Prabu; M. Kavitha; P. Nevathitha; A. Mathan Babu; D. Sarathapriya; L. Loveson Edward; et al. (Regional Studies in Marine Science, 2026)

Luteolin Modulates DNA Methylation and Histone Acetylation To Restore Nrf2 and Alleviate Hyperglycemia-Induced Oxidative Stress in Vitro - Srinivasaragavan Divyajanani; Kannan Harithpriya; Kunka Mohanram Ramkumar (Cell Biochemistry and Biophysics, 2026)

Parameterization of Geomechanical Properties Through ML Algorithms for Accurate Determination and Prediction of Horizontal Stress: A Case of Niger Delta Basin and Implications on Its Application - Oluwaseun Daniel Akinyemi; John Oluwadamilola Olutoki; Mohamed Elsaadany; Numair Ahmed Siddiqui; Sami ElKurdy; Muthuvairavasamy Ramkumar (Pure and Applied Geophysics, 2026)

A summary of the Lucy Ashton resistance prediction workshop - Rui Lopes; Arash Eslamdoost; Rickard E. Bensow; Dmitriy Ponkratov; Anja Kömpe; Paolo Geremia; Çagan Birant Pekküçük; Cagri Aydin; Diego Villa; Dimitris Ntouras; Dong Cheol Seo; Gennaro Rosano; et al. (Ocean Engineering, 2026)

Tracing anthropogenic signatures of heavy metal dispersion and risk profiling in marine sediments of tuticorin’s industrial coast - Vigneshwar Jeyasingh; Ramkumar Thirunavukkarasu; Vasudevan Sivaprakasam; Sathiyamoorthy Gunasekaran; Baranidharan Sathyanarayanan; Pravinraj Sampath; Venkatramanan Senapathi; Anandasabari Karthikeyan (Ocean Dynamics, 2026)

Elemental Imbalance in Disease Pathogenesis: The Promise of Chelating Peptides as Therapeutic Targets - Jayavigneeswari Suresh babu; Lingam Gopal; Ramkumar Km; Bharathidevi Subramaniam Rajesh (International Journal of Peptide Research and Therapeutics, 2025)

Fabrication of PES membranes using pure and mixed aprotic solvents (DMSO-DMAc) for enhanced membrane distillation - N. Ramkumar; P. Monash (Journal of Environmental Chemical Engineering, 2025)

Oleo gum resin extracts of Commiphora wightii negatively impact the activity of recombinant human lipoprotein lipase - Piyush Wamanrao Ghoshe; Anuraga Pathmarajan; Gopi Vidyasagar; Veeraraghavan Priyanka; Kunka Mohanram Ramkumar; Dronamraju V.L. Sarada (Biocatalysis and Agricultural Biotechnology, 2025)

Phytomolecule-doped green synthesis of Ag@Fe bimetallic nanocomposites from Abutilon indicum leaf extract: Antimicrobial activity against Mycobacterium spp. and pathogenic bacteria and their cytotoxicity assessment in zebrafish embryos - Mary Shamya Arokiarajan; J. John Christopher; S. Ranjani; S.A. Wasim Akram; K.M. Ramkumar; S. Tirumala Santoshkumar; Noman Anwar; T. Rajaseker; M Radhakrishnan; V. Muzammil Ahmed; Murali Krishna Prasad; K. Kabiruddin Ahmed; et al. (Biocatalysis and Agricultural Biotechnology, 2025)

Metal Footprints Imprinted in the Textural Traits of Mullakadu Beach Sediments, Tuticorin Coast, India - Vigneshwar Jeyasingh; Ramkumar Thirunavukkarasu; Vasudevan Sivaprakasam; Sathiyamoorthy Gunasekaran; Baranidharan Sathyanarayanan; Venkatramanan Senapathi (Water, Air, & Soil Pollution, 2025)

Genetic Validation of Marphysa mossambica (Peters, 1854) from the West Coast of India - Kenyum Lollen; Sukham Munilkumar; Thongam Ibemcha Chanu; Ramkumar Sugumar; Upasana Sahoo; Layana Porayil; Sonam Angmo (Thalassas: An International Journal of Marine Sciences, 2025)

Targeted disruption of OsBADH2 induces basmati aroma in the popular indica rice variety IR-64 using CRISPR/Cas9 - Vacha Bhatt; Thakku R. Ramkumar; Vitthal Barvkar; Rupesh Deshmukh; Gunvant B. Patil; Altafhusain Nadaf (Plant Physiology Reports, 2025)

Molecular insights into melatonin-mediated stress tolerance in rice - Ill-Min Chung; Muthu Thiruvengadam; Ramkumar Samynathan; Seung-Bin Lee; Hee-Jin Choi; Bum-Su Jung; Yunwoo Park; Dagyeom Jeon; Baskar Venkidasamy; Seung-Hyun Kim (Plant Cell Reports, 2025)

Role of inflammasomes in diabetes mellitus: mechanisms, complications, and therapeutic potential - K. L. Milan; Bhatnagar Megha; K. M. Ramkumar (Molecular Biology Reports, 2025)

Acaricide resistance and possible underlying biochemical mechanisms in the two-spotted spider mite, Tetranychus urticae Koch, on cut flowers - Sundaravadivel Sathiya Priya; Ettiappan Sumathi; Ramkumar Haran; Perumal Renukadevi; Marimuthu Murugan; Thirumalaiandi Ramasubramanian; K. K Kumar; S. P Thamarai Selvi; Sivakumar Kowsika (Ecotoxicology, 2025)

Performance of timber-concrete composite members: a Study on connectors and failure modes - Pablo Ochoa; Siva Avudaiappan; Aitor Cendoya; Nelson Maureira-Carsalade; Manuel Chávez; Cristian Canales; V. R. Ramkumar; H. Patricio Cendoya (Journal of the Indian Academy of Wood Science, 2025)

Multi-instrument observations of unseasonal post-sunset equatorial plasma bubbles during two moderate geomagnetic storms in May and June 2024 over East/Southeast Asia - Sampad Kumar Panda; Siva Sai Kumar Rajana; Chiranjeevi G. Vivek; Ramkumar Vankadara; Punyawi Jamjareegulgarn (Advances in Space Research, 2025)

Nicotinamide riboside supplementation restores microglial health and improves cognition in aged male mice - Ramkumar Thiyagarajan; Rupadevi Muthaiah; Bhavana Sreevelu; Owen P. Treanor; Yonas Redae; Reem Berman; Anna L. Davis; Nanda Yellapu; Spencer R. Rosario; Lee D. Chaves; Kenneth L. Seldeen; Bruce R. Troen (GeroScience, 2025)
Cognitive impairment affects 1 in 6 individuals over 60, with over 75 million projected by 2030. Age-related changes in microglial function and declining nicotinamide adenine dinucleotide (NAD + ) levels may contribute to cognitive decline. Although nicotinamide riboside (NR) supplementation can restore NAD + levels in aged mice, its effects on microglial phenotype and cognition during normal aging remain unclear. We assessed cognitive function, neuroinflammation, and microglial gene expression in 6-month (Young) and 22-month (Aged) mice, along with aged mice supplemented with NR (Aged + NR; 400 mg/kg body weight) for 8 weeks. Aged mice exhibited impaired cognition and increased gene expression related to neuroinflammation. NR supplementation improved or prevented the decline in nest-building ability, Y-maze spontaneous alternation, and novel object recognition, which are reflective of instrumental activities of daily living, spatial working memory, and recognition memory. NR supplementation diminished microglial (IBA1) and astrocytic (GFAP) activation, resembling the young phenotype. Gene expression profiling revealed reduced microglial activation, inflammatory pathways, and chemokine production in Aged + NR mice, along with upregulation of genes associated with learning, memory, and gliogenesis. NR lowered transcriptional signatures from age-dependent (ADEM) and disease-associated (DAM) microglia and enhanced homeostatic state profiles. Metabolic pathway analysis of microglial transcripts indicated that NR suppressed age-induced increases in fatty acid metabolism. This was supported by immunostaining, which showed reduced lipoprotein lipase (LPL), a DAM marker, in the cortex and hippocampus. Overall, NR appeared to mitigate age-related cognitive decline by shifting microglial gene expression and metabolism toward a younger phenotype, suggesting potential therapeutic relevance for healthy brain aging.

Unveiling microplastic contamination in seafood: Source, fate, analytical methods, health impacts, mitigation strategies and scientometric trends - Ulaganathan Arisekar; E. Arivukumar; Abuthagir Iburahim; Rajendran Shalini; Balasubramanian Sivaraman; Manickam Selvaraj; Hamed A. Ghramh; Bhagyalakshmi Kalidass; Vijayakumar Renuka; S. Ramkumar (Marine Pollution Bulletin, 2025)

Fetal response to maternal exposures of environmental chemicals: Utility of a four-cell human feto-maternal interface organ-on-chip - Haley L. Moyer; SungJin Kim; Bowie P. Lam; Lauren S. Richardson; Han-Hsuan D. Tsai; Lucie C. Ford; Hsing-Chieh C. Lin; Weihsueh A. Chiu; Ramkumar Menon; Arum Han; Ivan Rusyn (Chemico-Biological Interactions, 2025)

Identification of GPX3 as a key biomarker of placental ferroptosis in gestational diabetes mellitus via bioinformatics and clinical analysis - Padmanaban M. Abirami; K. L. Milan; M. Anuradha; Kunka Mohanram Ramkumar (Molecular Diversity, 2025)

Engineering synergistic electrocatalysts via plastic derived disodium terephthalate on Ti3C2Tx / nickel foam for enhanced HER performance - Rahul Ramkumar; Seung Geun Jo; Jung Woo Lee (Journal of Environmental Chemical Engineering, 2025)

Synthesis and characterization of lanthanum-assisted aluminium metal-organic frameworks for the removal of fluoride ions from an aqueous environment - S. Anu Ratthika; K. Ramkumar; S.SD. Elanchezhiyan; Rajesh Kumar; S. Meenakshi (Journal of Environmental Chemical Engineering, 2025)

Orexin Receptor Antagonists and Insomnia - Jayaram Saibaba; Ramkumar Sugumaran (Sleep and Vigilance, 2025)

Exosome-Mediated Delivery of a PLD1 Modulator Overcomes Bioavailability Hurdles to Target Synaptopathy in Neurodegenerative Diseases - Shaneilahi Budhwani; Sravan Gopalkrishna Shetty Sreenivasamurthy; Klarissa H. Garza; Pilar Flores-Espinosa; Ramkumar Menon; Ananth Kumar Kammala; Balaji Krishnan (Pharmaceutical Research, 2025)

Eco-friendly bio-larvicidal and antimicrobial activity of isolated bioactive compound from Kurthia gibsonii (Bacillales) - Dhayalan Arul; Govindasamy Vinoth; Ranganathan Muthusamy; Thillainathan Natarajan; Chinnaperumal Kamaraj; Paramasivam Deepak; Sundaramoorthy Dhanasundaramd; Pachiappan Perumal; Govindaraju Ramkumar (Natural Product Research, 2025)

Quantifying coastal cliff retreat, sediment volume, and dynamics using photogrammetry and geospatial analysis in the Pénestin Peninsula, France - David Menier; Romain Le Gall; Manoj Joseph Mathew; Benjamin Sautter; Mu. Ramkumar; Effi Helmy Ariffin; Glen Bulot; Franto Novico; Guilhem Estournès; Céline Le Mignant (Geomorphology, 2025)

Biocontrol potential and characterization of cell-free supernatants from Xenorhabdus nematophila: A novel approach to control Tetranychus urticae - Sundaravadivel Sathiya Priya; Thirunavukarasu Deeikshana; Ramkumar Haran; Ganeshan Shandeep; Subramanian Pradeep; Ettiappan Sumathi (Crop Protection, 2025)

Transforming farming: mutational breeding as a sustainable solution for crop improvement in the 21st century - Navyanjani Kavuri; Hemasundar Alavilli; Ramkumar Manthari; Byeong-ha Lee; Satendra Kumar Mangrauthia (Journal of Plant Biochemistry and Biotechnology, 2025)

Eco-friendly synthesis of silver nanoparticles from the red seaweed Gelidiella acerosa and their impact on larvae of Anopheles stephensi, Aedes aegypti, and Culex quinquefasciatus - Annamalai Aravinth; Prasobh K. Mohan; Mohankumar Narayanan; Pachiappan Perumal; Sundaramoorthy Dhanasundaram; Rajaram Ramkumar; Chinnaperumal Kamaraj; Rajendran Rajaram (Journal of Applied Phycology, 2025)

Exploring the utilization potential of Lantana camara: particleboard and briquette development - V. R. Ramkumar; K. Thanigai; Ritesh Kumar; G. Murali; V. Prakash; Veer Singh Gautam; Manish Ranjan; Narasimha Murthy (Journal of the Indian Academy of Wood Science, 2025)

Role of oxeiptosis in disease mechanisms and therapeutic opportunities - K. Bhuvaneshwari; Kannan Harithpriya; Kumar Ganesan; Baojun Xu; Kunka Mohanram Ramkumar (Apoptosis, 2025)

Protective effects of madecassoside, a triterpenoid from Centella asiatica , against oxidative stress in INS-1E cells - Swee Ching Tan; Ramkumar Rajendran; Subrat Kumar Bhattamisra; Purushotham Krishnappa; Fabian Davamani; Ebenezer Chitra; Stephen Ambu; Brian Furman; Mayuren Candasamy (Natural Product Research, 2025)

Nanoemulsified formulation of cell-free supernatant from Photorhabdus luminescens as a sustainable biopesticide against Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) - V.P. Krithika; Anita Bellie; Ramkumar Haran; Deeikshana Thirunavukarasu; Shandeep Ganeshan; C. Sankaranarayanan; Prabhu Somasundaram; M. Suganthy; Gomathi V (Crop Protection, 2025)

Chemical engineering innovations in nanoparticle-based biosensors for enhanced detection of biological molecules - Ramkumar Vanaraj; Bharathi Arumugam; Gopiraman Mayakrishnan; Santhanaraj Daniel; Cadiam Mohan Babu; Seong Cheol Kim (Chemical Engineering Journal, 2025)

Application of quality by design in optimization of nanoformulations: Principle, perspectives and practices - Devendra Birla; Nikhil Khandale; Bushra Bashir; Md. ShahbazAlam; Sukriti Vishwas; Gaurav Gupta; Harish Dureja; Popat S. Kumbhar; John Disouza; Vandana Patravale; Francisco Veiga; Ana Cláudia Paiva-Santos; et al. (Drug Delivery and Translational Research, 2025)

Climate Change Impact on Geographical Region and Healthcare Analysis Using Deep Learning Algorithms - Ganduri Srikanth; Ch V. Raghavendran; M. Ramkumar Prabhu; Marepalli Radha; N. V. Siva Kumari; Sabitha Kumari Francis (Remote Sensing in Earth Systems Sciences, 2025)

Textural characteristics of channel bed sediments and heavy minerals of the Cauvery River, Southern India: implications on depositional environments, provenance, tectonics and climate - M. Ramkumar; AL Fathima; G. Sugavanam; B. Velliyangiri; M. Selvakumar; S. Anbarasan; M. Sowmiya; S. Kiruthika; K. Balasubramani; V. Thirukumaran; P. D. Roy; R. Nagarajan; et al. (Journal of Sedimentary Environments, 2025)

Correction: Exploration of bioactive molecules from Sesbania grandiflora (L.): identification of squalene as an effective compound against the two-spotted spider mite, Tetranychus urticae Koch, through molecular docking - S. S. Praveen Joshi; Ettiappan Sumathi; Marimuthu Murugan; Ramkumar Haran; Sundaravadivel Sathiya Priya; Ganeshan Shandeep; Subbarayalu Mohankumar; Doraiswamy Uma; Ashitha Nelson (Experimental and Applied Acarology, 2025)

Direct solid–vapor approach to 2D FeCoNiP@N-graphene-CNTs as robust electrode material for high-performance supercapacitors - Gopiraman Mayakrishnan; Ramkumar Vanaraj; Seong Cheol Kim; Ick Soo Kim (Chemical Engineering Journal, 2025)

Addressing the Microplastic Pollution: A Societal Challenge - Minisha Udhayakumar; Shanmugapriya Udhayakumar; Subha Bharathi Pitchaimuthu; Sandhya Alagarsamy; Kayalvizhi Thirumalaisamy; Muhammad Azeem; Ramkumar Govindarajan; Karthiyaini Damodharan; Ayyappa Das Madhubala Parameswaran; Parimala Gnana Soundari Arockiam Jeyasundar (Water, Air, & Soil Pollution, 2025)

Exploration of bioactive molecules from Sesbania grandiflora (L.): identification of squalene as an effective compound against the two-spotted spider mite, Tetranychus urticae Koch, through molecular docking - S. S. Praveen Joshi; Ettiappan Sumathi; Marimuthu Murugan; Ramkumar Haran; Sundaravadivel Sathiya Priya; Ganeshan Shandeep; Subbarayalu Mohankumar; Doraiswamy Uma; Ashitha Nelson (Experimental and Applied Acarology, 2025)

Symbiosis in Sea Anemones: A Few Case Reports Along the Bay of Bengal Large Marine Ecosystem - L. Ranjith; R. Saravanan; S. Ramkumar; C. Kalidas; R. Vinothkumar; D. Linga Prabu; M. Kavitha; A. Mathan Babu; R. Kalaibharathi; P. S. Asha (Marine Ecology, 2025)
The most well‐known relationship is between sea anemones and decapod crustaceans, of which crabs are classic examples of mutualistic interactions in which both organisms benefit from living with zooxanthellae and hermatypic or reef‐forming corals. A marine ecology study off the southern coast of Tamil Nadu revealed five types of sea anemones that cohabit symbiotically with other marine animals. These species include Stichodactyla haddoni (Saville‐Kent, 1893), Entacmaea quadricolor (Leuckart in Ruppell and Leukart, 1828), Radianthus (= Heteractis ) magnifica (Quoy and Gaimard, 1833), Radianthus (= Heteractis ) crispa (Ehrenberg, 1834), and Calliactis polypus (Forsskal, 1775), are found in symbiotic associations. This observation revealed that the decapod porcelain crab Neopetrolisthes is associated with the sea anemones Radianthus and Entacmaea , whereas this has not been reported in Stichodactyla . The hermit crab anemone, C. polypus , is generally associated with hermit crabs, and we report this association for the first time in live gastropod, Turbinella pyrum (Linnaeus, 1767). A few animals (both the host and symbiont) were brought to the cnidarian laboratory at the ICAR‐Tuticorin Regional Station of the CMFRI, where they were maintained in optimum seawater for further observations. The present study aimed to compare previous reports of symbiosis in decapod crustaceans and gastropods with sea anemones from Indian waters to provide insight into the dynamics of symbiosis in the Bay of Bengal Large Marine Ecosystem.

Molecular dynamics exploration of cacophony protein interactions with brood volatiles in honey bee colonies - Ramkumar Haran; Ettiappan Sumathi; Chakkarai Sathyaseelan; Mannu Jayakanthan; Ganeshan Shandeep; Sundaravadivel Sathiya Priya; Eswaran Kokiladevi; V.P. Krithika (Journal of Asia-Pacific Entomology, 2024)

Unraveling the enigma: chronic kidney disease of unknown etiology and its causative factors with a specific focus on dissolved organic compounds in groundwater—reviews and future prospects - Madhumitha Kumaresan; Anjali Vijayan; Mu. Ramkumar; Neena Elezebeth Philip (Environmental Geochemistry and Health, 2024)

Autosomal recessive spastic ataxia of charlevoix-saguenay (ARSACS)-first with tongue wasting, peripheral nerve thickening and a novel SACS gene mutation - Ramkumar Sugumaran; Ragavendar Bhuvaneswaran; Sunil K. Narayan (Acta Neurologica Belgica, 2024)

Retraction Note: ROS-mediated cytotoxic activity of ZnO and CeO2 nanoparticles synthesized using the Rubia cordifolia L. leaf extract on MG-63 human osteosarcoma cell lines - Natarajan Sisubalan; Vijayan Sri Ramkumar; Arivalagan Pugazhendhi; Chandrasekaran Karthikeyan; Karuppusamy Indira; Kasi Gopinath; Abdulrahman Syedahamed Haja Hameed; Mohamed Hussain Ghouse Basha (Environmental Science and Pollution Research, 2024)

Understanding the role of Bacillus subtilis GEB1 in enhancing guava plant immunity against Meloidogyne enterolobii: A multifaceted approach - Shandeep Ganeshan; Shanthi Annaiyan; Jayakanthan Mannu; Vijay Settu; Gayathri Muthusamy; Arunachalam Arun; Prabhu Somasundaram; Ramkumar Haran; V.P. Krithika; Saravanan Ravi; Deeikshana Thirunavukarasu (Physiological and Molecular Plant Pathology, 2024)

A coverage path planning approach for environmental monitoring using an unmanned surface vehicle - Sanjeev Kumar Ramkumar Sudha; Deepti Mishra; Ibrahim A. Hameed (Ocean Engineering, 2024)

Unveiling novel applications of fruit pomace for sustainable production of value-added products and health benefits: A review - Baskar Venkidasamy; Ramkumar Samynathan; Pasiyappazham Ramasamy; M.P. Santhosh Kumar; Muthu Thiruvengadam; Mars Khayrullin; Mohammad Ali Shariati; Arti Shivraj Nile; Shivraj Hariram Nile (Food Bioscience, 2024)

Effect of Bis (methyl glycol) phthalate on endoplasmic reticulum stress in endothelial cells - Verma Nishitha-Hiresha; Raghavan Varsha; S. Srinidhi; Ravichandran Jayasuriya; Kannan Harithpriya; Paromita Chakraborty; Kunka Mohanram Ramkumar (Environmental Toxicology and Pharmacology, 2024)

Production of gluconic acid from the washed rice waste water using Au/MgO catalyst – A sustainable route - Pavithra Muthu Batcha; Ramkumar Vanaraj; Seong-Cheol Kim; Rajakumar Kanthapazham; Rajendran Annamalai; Santhanaraj Daniel (Bioresource Technology, 2024)

A practical approach to meeting national obligations for sustainable trade under CITES - Tanvi Vaidyanathan; Sarah J. Foster; B. Ramkumar; Amanda C. J. Vincent (Conservation Biology, 2024)
Reconciling conservation goals with sustainable resource use requires adaptive management strategies. The Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) regulates global trade for species listed on Appendix II, partly by requiring member countries (parties) to ensure exports do not damage wild populations (called making positive “nondetriment findings” [NDFs]). Unfortunately, when parties find NDFs difficult, they often suspend legal trade, imposing economic costs and driving trade underground. To make it easier for parties to examine the detrimental nature of exports, we devised a spatial approach and applied it to seahorses ( Hippocampus spp.) in Tamil Nadu, India, as an example. Our approach involves mapping answers to 5 key questions on species distribution (QA), pressures (QB), management measures (QC), management implementation (QD), and species’ population status (QE). We gathered data from fisher interviews and published literature. Seahorse abundance was greatest in southern Palk Bay and the northern Gulf of Mannar, primarily in seagrasses and coral reefs (QA). Fishing pressure was highest in Palk Bay, primarily from bottom trawlers and dragnetters operating in shallow seahorse habitats near the coastline (QB). Management measures including a marine protected area (MPA), bottom trawl exclusion zone, and closed season were theoretically in place (QC), but their implementation was poor (QD). Fishers reported seahorse catches in 85% of the area covered by the MPA and the exclusion zone; bottom trawlers were responsible for most violations. Seahorses were also captured in Sri Lankan waters, where bottom trawling is banned. Fisher reports indicated declining seahorse catches and reduced body sizes (QE), highlighting unsustainable exploitation. Our results highlight the need for better implementation of existing management measures before a positive NDF can be made and suggest mitigation beyond bans. Such pragmatic spatial analyses can help regulate exports at sustainable levels, supporting CITES implementation for its vast range of species.

Molecular Mechanism of NL13 Peptide of Adenosyl Homocysteinase Against ER Stress through Nrf2 Signaling Cascade - Purabi Sarkar; Karan Naresh Amin; Ranjith Balakrishnan; Kunka Mohanram Ramkumar; Jesu Arockiaraj (International Journal of Peptide Research and Therapeutics, 2024)

Genomic analysis of Bacillus subtilis sub sp. subtilis GEB5 reveals its genetic assets for nematicidal and plant growth promoting mechanisms - Shandeep Ganeshan; Vijay Settu; Jayakanthan Mannu; Shanthi Annaiyan; Gayathri Muthusamy; Arunachalam Arun; Prabhu Somasundaram; Haran Ramkumar; V.P. Krithika (Rhizosphere, 2024)

Genome mining of Photorhabdus luminescens TNAU1 reveals novel gene assets with insecticidal and nematicidal properties - V.P. Krithika; Anita Bellie; Ganeshan Shandeep; Vijay Settu; Deeikshana Thirunavukkarasu; Haran Ramkumar; C. Sankaranarayanan; Prabhu Somasundaram; K. Devrajan (Physiological and Molecular Plant Pathology, 2024)

Effect of hybrid steel fibres on shear behaviour of self compacting RC beam - K. B. Ramkumar; C. Sudha; K. Gunasekaran; P. R. Kannan Rajkumar (Innovative Infrastructure Solutions, 2024)

Exploring the link between convectively generated gravity waves and ionospheric anomalies: Insights from observations near the low-mid latitude geomagnetic transition region - Mohammad Rafeeq Rather; Aashiq Hussain Bhat; T.K. Ramkumar; Manzoor A. Malik (Advances in Space Research, 2024)

Coastal resilience and shoreline dynamics: assessing the impact of a hybrid beach restoration strategy in Puducherry, India - Judha Benhur; Mullai Vendhan; Phani Kumar; Ramkumar Janagiraman (Frontiers in Marine Science, 2024)
Puducherry, a Union Territory of India, has been strongly affected by severe erosion after the construction of the Puducherry port in 1989. To mitigate this cause, the National Institute of Ocean Technology, Chennai, and the Puducherry government implemented a beach restoration strategy involving a hybrid solution in 2017 for coastal protection/stabilization and the restoration of the lost beach. The strategy involved deploying a steel reef into the nearshore sea and implementing beach nourishment processes. To monitor the coastal morphological changes after implementing the coastal protection strategy, the Digital Shoreline Analysis System, was adopted to calculate the rate of shoreline change statistics for the years 2016 to 2022. It uses spatio-temporal shoreline positions from multi-temporal satellite imagery. The shorelines are extracted from the Sentinel-2A satellite images by a Normalized Differential Water Index based semi-automated model. Statistical parameters in DSAS analyze the shorelines to determine the shoreline changes in this area. The results reveal the remarkable resilience of a newly restored beach, where the linear regression rate statistics in Zone A show an average accretional rate of 2.92m/yr. Alternatively, Zone B exhibits an average erosion rate of -0.23m/yr, with intermittent sandy beaches experiencing maximum erosion rates of -1.63m/yr. The influence of longshore current direction and sediment transport on shoreline movement is evident in seasonal analysis, with shoreline development and recession primarily observed near shore protection structures. The study’s outcome provides valuable insights for coastal management, offering a reliable approach for shoreline monitoring post-implementation of mitigation projects.

Thermochemical modeling and performance evaluation of freeze desalination systems - Aly Elhefny; Hamidreza Shabgard; Jie Cai; Reza Kaviani; Ramkumar N. Parthasarathy (Desalination, 2024)

Experimental investigation of mechanical properties and multi-objective optimization of electronic, glass, and ceramic waste–mixed concrete - Deivasigamani Uma Mageswari; Hakim Kareemullah; Korothan Jithesh; Sampath Boopathi; Paul Manoharan Premkumar Priya Rachel; Mathiyalagan Siva Ramkumar (Environmental Science and Pollution Research, 2024)

Exploiting the nematicidal compounds from guava endo microbiome against root-knot nematodes, Meloidogyne enterolobii - Ganeshan Shandeep; Shanthi Annaiyan; Ramkumar Haran; Jayakanthan Mannu; Prabhu Somasundaram; Haripriya Shanmugam; Angappan Kathithachalam; Arunachalam Arun (Physiological and Molecular Plant Pathology, 2024)

Forecasting influent wastewater quality by chaos coupled machine learning optimized with Bayesian algorithm - D. Ramkumar; V. Jothiprakash (Journal of Water Process Engineering, 2024)

Experimental and theoretical study of a novel freeze desalination system with an intermediate cooling liquid - Reza Kaviani; Hamidreza Shabgard; Aly Elhefny; Jie Cai; Ramkumar Parthasarathy (Desalination, 2024)

Multifunctional Nanocarriers for Alzheimer’s Disease: Befriending the Barriers - Mohammad Azam Ansari; Takshashila Tripathi; Baskar Venkidasamy; Alan Monziani; Govindasamy Rajakumar; Mohammad N. Alomary; Sami A. Alyahya; Oriane Onimus; Naomi D’souza; Md. Abul Barkat; Ebtesam A. Al-Suhaimi; Ramkumar Samynathan; et al. (Molecular Neurobiology, 2024)

In silico approach for the identification of tRNA-derived small non-coding RNAs in SARS-CoV infection - Swati Ajmeriya; Deepak Ramkumar Bharti; Amit Kumar; Shweta Rana; Harpreet Singh; Subhradip Karmakar (Journal of Applied Genetics, 2024)

Short-chain fatty acid: An updated review on signaling, metabolism, and therapeutic effects - Kaliaperumal Rekha; Baskar Venkidasamy; Ramkumar Samynathan; Praveen Nagella; Maksim Rebezov; Mars Khayrullin; Evgeny Ponomarev; Abdelhakim Bouyahya; Tanmay Sarkar; Mohammad Ali Shariati; Muthu Thiruvengadam; Jesus Simal-Gandara (Critical Reviews in Food Science and Nutrition, 2024)

A Graph Convolutional Network Approach to Qualitative Classification of Hydrocarbon Zones Using Petrophysical Properties in Well Logs - B. Venkateshwaran; Mu. Ramkumar; Numair Ahmed Siddiqui; AKM Eahsanul Haque; G. Sugavanam; A. Manobalaji (Natural Resources Research, 2024)

Diffusion of organochlorine (OCPs) and cypermethrin pesticides from rohu (Labeo rohita) internal organs to edible tissues during ice storage: a threat to human health - Ulaganathan Arisekar; Robinson Jeya Shakila; Rajendran Shalini; Balasubramanian Sivaraman; Arjunan Karthy; Mysoon M. Al-Ansari; Nora Dahmash Al-Dahmash; R. Mythili; Woong Kim; Sugumar Ramkumar; Bhagyalakshmi Kalidass; Shannon N. Sangma (Environmental Geochemistry and Health, 2024)

Biomonitoring of mercury and selenium in commercially important shellfish: Distribution pattern, health benefit assessment and consumption advisories - Ulaganathan Arisekar; Rajendran Shalini; Soundar Abuthagir Iburahim; S. Deepika; C. Prabhanjan Kumar Reddy; Kanagaraja Anantharaja; Mohammed F. Albeshr; Sugumar Ramkumar; Bhagyalakshmi Kalidass; K. Tamilarasan; N. Nandha Kumar (Environmental Geochemistry and Health, 2024)

Unique observations and interactions over the low-mid latitude transition region: Simultaneous study of plasma blobs, MSTIDs and plasma irregularities - Mohammad Rafeeq Rather; Aashiq Hussain Bhat; T.K. Ramkumar; Manzoor A. Malik (Advances in Space Research, 2024)

Determination of microplastics in the wetlands of specific regional area and unveiling the toxic properties of predominant HDPE particle on animal and plant models - Vijayakumar Aishwarya; Chinnannan Karthik; Kannan Maharajan; Kadirvelu Krishna; Ponmurugan Karuppiah; Jothi Ramalingam Rajabathar; Govindaraju Ramkumar; Ranganathan Keerthana (Process Safety and Environmental Protection, 2024)

Resistance to synthetic pyrethroid and neonicotinoid is associated with reduced reproductive efficiency in the field population of Spodoptera litura (Insecta: Lepidoptera) - Ranganathan Muthusamy; Govindaraju Ramkumar; Suresh Kumarasamy; Mohammed F. Albeshr; Abdulwahed Fahad Alrefaei; Ying Ma; Mathiyazhagan Narayanan (Biocatalysis and Agricultural Biotechnology, 2024)

Pixel Reduction of High-Resolution Image Using Principal Component Analysis - Ramachandran Radhakrishnan; Manimegalai Thirunavukkarasu; R. Thandaiah Prabu; G. Ramkumar; S. Saravanakumar; Anitha Gopalan; V. Rama Lahari; B. Anusha; Shaik Hasane Ahammad; Ahmed Nabih Zaki Rashed; Md. Amzad Hossain (Journal of the Indian Society of Remote Sensing, 2024)

A comprehensive review of beetroot ( Beta vulgaris L.) bioactive components in the food and pharmaceutical industries - Muthu Thiruvengadam; Ill-Min Chung; Ramkumar Samynathan; S. R. Harish Chandar; Baskar Venkidasamy; Tanmay Sarkar; Maksim Rebezov; Olga Gorelik; Mohammad Ali Shariati; Jesus Simal-Gandara (Critical Reviews in Food Science and Nutrition, 2024)

Combination effect of azadirachtin and chlorantraniliprole with three synergists against a serious invasive agricultural pest Spodoptera frugiperda (Lepidoptera: Noctuidae) - Ranganathan Muthusamy; Govindaraj Vengateswari; Suresh Kumarasamy; Ramkumar Pandi; N.R. Prasannakumar; Dhayalan Arul; Rajendran Dhanapal; B. Kariyanna; Chinnannan Karthik; Govindhan Malathi; Govindaraju Ramkumar (Biocatalysis and Agricultural Biotechnology, 2024)

A chaotic investigation on pollutant parameters of a wastewater treatment facility using false nearest neighbour algorithm - D. Ramkumar; V. Jothiprakash (Stochastic Environmental Research and Risk Assessment, 2024)

Chronic inflammatory axonal polyneuropathy with myositis: a rare presentation - B. Ragavendar; Ramkumar Sugumaran; Sunil K. Narayan; B. H. Srinivas (Acta Neurologica Belgica, 2023)

Biosynthesis, functional perspectives, and agricultural applications of strigolactones - Ramkumar Samynathan; Baskar Venkidasamy; Mohammad Ali Shariati; Pandiyan Muthuramalingam; Muthu Thiruvengadam (Brazilian Journal of Botany, 2023)

A remarkable oxygen vacancy-rich rare earth aerogel with high activity towards electro and catalytic reduction of 5-nitroquinoline - Ramya Ramkumar; Chellakannu Rajkumar; Heeyeon Do; Haekyoung Kim; Woo Kyoung Kim (Journal of Cleaner Production, 2023)

Physico-chemical Properties of the Vettar Estuarine Waters, Cauvery Basin, Southern India: Implications for Environmental Management - Deepthi Nanjappa; K P Devaganga; Mu Ramkumar; R Nagarajan; K Balasubramani (Thalassas: An International Journal of Marine Sciences, 2023)

Zinc and L-carnitine combination with or without methotrexate prevents intestinal toxicity during arthritis treatment via Nrf2/Sirt1/Foxo3 pathways: an In vivo and molecular docking approach - Ramkumar Katturajan; Sabina Evan Prince (Inflammopharmacology, 2023)

Developments in analytical techniques for chemostratigraphy, chronostratigraphy, and geochemical fingerprinting studies: Current status and future trends - Balaram V; Ramkumar M; Akhtar R. Mir (Journal of South American Earth Sciences, 2023)

Ensemble classifier fostered detection of arrhythmia using ECG data - M. Ramkumar; Manjunathan Alagarsamy; A. Balakumar; S. Pradeep (Medical & Biological Engineering & Computing, 2023)

Impact assessment of natural variations in different weather factors on the incidence of whitefly, Bemisia tabaci Genn. and yellow vein mosaic disease in Abelmoschus esculentus (L.) Moench - Radheshyam Ramakrishna Dhole; Rajendra Nath Singh; Rajendran Dhanapal; Saurav Singla; Govindaraju Ramkumar; Ranganathan Muthuusamy; Saleh H. Salmen; Sulaiman Ali Alharbi; Mathiyazhagan Narayanan; Indira Karuppusamy (Environmental Research, 2023)

Effect of melatonin and luzindole antagonist on fipronil toxicity, detoxification and antioxidant enzyme system in different tissues of Helicoverpa armigera (Lepidoptera: Noctuidae) - Ranganathan Muthusamy; Govindaraju Ramkumar; Suresh Kumarasamy; Thimmappa Chethan Kumar; Mohammed F. Albeshr; Abdulwahed Fahad Alrefaei; Tran Cam Nhung; Barani B; Indira Karuppusamy (Environmental Research, 2023)

Synergism and toxicity of iron nanoparticles derived from Trigonella foenum-graecum against pyrethriod treatment in S. litura and H. armigera (Lepidoptera: Noctuidae) - Ranganathan Muthusamy; Govindaraju Ramkumar; Suresh Kumarasamy; Nguyen Thuy Lan Chi; Sami Al Obaid; Saleh Alfarraj; Indira Karuppusamy (Environmental Research, 2023)

Association of nanoparticles and Nrf2 with various oxidative stress-mediated diseases - Rekha Thiruvengadam; Baskar Venkidasamy; Ramkumar Samynathan; Rajakumar Govindasamy; Muthu Thiruvengadam; Jin Hee Kim (Chemico-Biological Interactions, 2023)

Pterostilbene attenuates hemin-induced dysregulation of macrophage M2 polarization via Nrf2 activation in experimental hyperglycemia - Goutham V. Ganesh; Kunka Mohanram Ramkumar (Inflammopharmacology, 2023)

Dysfunctions, molecular mechanisms, and therapeutic strategies of pancreatic β-cells in diabetes - Murali Krishna Prasad; Sundhar Mohandas; Kunka Mohanram Ramkumar (Apoptosis, 2023)

Recent insights on tea metabolites, their biosynthesis and chemo-preventing effects: A review - Ramkumar Samynathan; Muthu Thiruvengadam; Shivraj Hariram Nile; Mohammad Ali Shariati; Maksim Rebezov; Raghvendra Kumar Mishra; Baskar Venkidasamy; Sureshkumar Periyasamy; Ill-Min Chung; Mirian Pateiro; José M. Lorenzo (Critical Reviews in Food Science and Nutrition, 2023)

Geochemical fractionation, mobility of elements and environmental significance of surface sediments in a Tropical River, Borneo - R. Nagarajan; Sellappa Gounder Eswaramoorthi; A. Anandkumar; M. Ramkumar (Marine Pollution Bulletin, 2023)

L-carnitine and Zinc supplementation impedes intestinal damage in methotrexate-treated adjuvant-induced arthritis rats: Reinstating enterocyte proliferation and trace elements - Ramkumar Katturajan; Sabina Evan Prince (Journal of Trace Elements in Medicine and Biology, 2023)

Discovery of pyrrolo[2,1-f][1,2,4]triazine-based inhibitors of adaptor protein 2-associated kinase 1 for the treatment of pain - Carolyn D. Dzierba; Bireshwar Dasgupta; George Karageorge; Walter Kostich; Brian Hamman; Jason Allen; Kim M. Esposito; Ramesh Padmanabha; James Grace; Kimberley Lentz; John Morrison; Daniel Morgan; et al. (Medicinal Chemistry Research, 2023)

Biorecognition elements appended gold nanoparticle biosensors for the detection of food-borne pathogens - A review - Sandhya Sadanandan; Meenakshi V. S; Keerthana Ramkumar; Neeraja P. Pillai; Anuvinda P; Sreelekshmi P. J; Devika V; Ramanunni K; Jeevan Sankar R; M.M. Sreejaya (Food Control, 2023)

Integrated system to reduce emissions from natural gas-fired reciprocating engines - Hafiz Ahmad Hassan; Matthew Hartless; Mohammed A.Moinuddin Ansari; Carlos D. Pena; James D. Lynch; Pejman Kazempoor; Ramkumar N. Parthasarathy (Journal of Cleaner Production, 2023)

Pigment composition analysis of fruit pulp in the recombinant progenies reveals the polygenic nature of pulp color inheritance in guava (Psidium guajava L.) - Madhubala Thakre; Hanamant S.; Ramkumar M.K.; Rutuparna Senapati; Shalini Gaur Rudra; Supradip Saha; A. Nagaraja; M. K. Verma; Gopala Krishnan S.; Eldho Varghese; Amitha Mithra Sevanthi (Tree Genetics & Genomes, 2023)

Ureaplasma parvum infection induces inflammatory changes in vaginal epithelial cells independent of sialidase - Emmanuel Amabebe; Lauren S. Richardson; Giovana Fernanda Cosi Bento; Enkhtuya Radnaa; Talar Kechichian; Ramkumar Menon; Dilly O. C. Anumba (Molecular Biology Reports, 2023)

Sustainable approach to manage the vulnerable rodents using eco-friendly green rodenticides formulation through nanotechnology principles – A review - S. Karthick Raja Namasivayam; Subramanian Srinivasan; Krishnappa Samrat; Bala Priyalakshmi; Ramkumar Dinesh Kumar; Arvind Bharani; Ramkumar Ganesh Kumar; M. Kavisri; Meivelu Moovendhan (Process Safety and Environmental Protection, 2023)

Emerging role of nutritional short-chain fatty acids (SCFAs) against cancer via modulation of hematopoiesis - Muthu Thiruvengadam; Umadevi Subramanian; Baskar Venkidasamy; Prabhu Thirupathi; Ramkumar Samynathan; Mohammad Ali Shariati; Maksim Rebezov; Ill-Min Chung; Kannan R. R. Rengasamy (Critical Reviews in Food Science and Nutrition, 2023)

Observations and mesoscale forecasts of the life cycle of rapidly intensifying super cyclonic storm Amphan (2020) - Jyoti Bhate; Amit Kesarkar; Arpita Munsi; Kasturi Singh; Asish Ghosh; Abhishek Panchal; Ramkumar Giri; M. M. Ali (Meteorology and Atmospheric Physics, 2023)

Correction to: Accumulation, Chronicity, and Induction of Oxidative Stress Regulating Genes Through Allium cepa L. Functionalized Silver Nanoparticles in Freshwater Common Carp (Cyprinus carpio) - Krishnasamy Sekar Rajkumar; Ramkumar Arunachalam; Murugadas Anbazhagan; Sivagaami Palaniyappan; Srinivasan Veeran; Arun Sridhar; Thirumurugan Ramasamy (Biological Trace Element Research, 2023)

Accumulation, Chronicity, and Induction of Oxidative Stress Regulating Genes Through Allium cepa L. Functionalized Silver Nanoparticles in Freshwater Common Carp (Cyprinus carpio) - Rajkumar Krishnasamy Sekar; Ramkumar Arunachalam; Murugadas Anbazhagan; Sivagaami Palaniyappan; Srinivasan Veeran; Arun Sridhar; Thirumurugan Ramasamy (Biological Trace Element Research, 2023)

Comparative assessment of leaf photosynthetic traits for improved carbon dioxide fixation in selected tree species of Pachamalai hills - Suganthi Kanagaraj; Maniraj Rathinam; M. K. Ramkumar; Rohini Sreevathsa; Govindaraju Munisamy (Brazilian Journal of Botany, 2023)

Nanoparticle assorted biofuels production from biowastes through transesterification - T. Sathish; R. Saravanan; M. Rajasimman; Ayman A. Ghfar; Vanaraj Ramkumar (Fuel, 2023)

In vitro somatic embryo productions from Curculigo orchioides derived gold nanoparticles: Synthesis, characterization, its biomedical applications, and their eco-friendly approaches to degradation of methylene blue under solar light irradiations - Kayalvizhi Thamilchelvan; Chinnasamy Ragavendran; Desingu Kamalanathan; Ramkumar Rajendiran; Tijo Cherian; Guilherme Malafaia (Environmental Research, 2023)

Anti-bacterial and arsenic remediation insights in aqueous systems onto heterogeneous metal oxide (Cu0.52Al0.1Fe0.47O4)/rGO hybrid: an approach towards airborne microbial degradation - Yaswanth K. Penke; Prem Anand Murugan; Saravanan Matheshwaran; Janakarajan Ramkumar; Kamal K. Kar (Environmental Science and Pollution Research, 2023)

A short review on sugarcane: its domestication, molecular manipulations and future perspectives - Kandhalu Sagadevan Dinesh Babu; Vardhana Janakiraman; Harunipriya Palaniswamy; Lakshmi Kasirajan; Raju Gomathi; Thakku R. Ramkumar (Genetic Resources and Crop Evolution, 2022)

Geochemical evolution of structure-bedding controlled hydrothermal dolomites of the Kinta Valley, Western Malaysia - P. Xin Hui; R. Nagarajan; Mu. Ramkumar; T. F. Ng; Nur I. Taib; M. J. Mathew; B. Sautter; N. A. Siddiqui; M. C. Poppelreiter (Carbonates and Evaporites, 2022)
Study of secondary dolomitization and documentation of the evolution of basinal fluids and host rock, especially that of fine-grained deepwater carbonate mudstone are of interest toward of reservoir characterization. From this perspective, field characteristics in relation to mineralogy, petrography and geochemistry of the Paleaozoic carbonates of the Kinta Valley, Peninsular Malaysia, were investigated and documented. A total of 33 samples were collected across the various degree of dolomitization and analyzed for their petrographic properties ( n = 55), while mineralogical and geochemical compositions ( n = 33) were analyzed using XRD, ICP and ICPMS analysis, respectively. These analyses were performed to elucidate the diagenetic events, episodic dolomitization and development of fluid evolution as a function of regional tectono-thermal events during the Permian to Cenozoic. It is interpreted that the host calcareous mudstones (HCMs) were deposited in oxygenated, open marine seawaters. The studied samples retain the original seawater characteristics despite negligible, minor alterations of REE characteristics due to diagenesis and detrital input. Though the concentrations and trends of REEs of the dolomitic facies are modified to a certain extent, their affinities with HCMs are preserved. Enrichments of Mg, Mn, Na and depletion of Sr are linked to the effect of dolomitization under the open system of diagenesis. The redox conditions fluctuated to show distinct, recognizable variations between different dolomite phases. The MREE enrichments with other trace elements such as Mn, Fe and low Sr content indicate the association of diagenetic fluids with deep-circulating crustal hydrothermal fluids. Hydrothermal influence has been recorded along the fractures, which might have originated from the sub-surface litho units and facilitated episodic dolomitization, especially during significant tectono-thermal events. This study affirms that the occurrence, geochemical and mineralogical evolution of the dolomites of the Kinta Valley were controlled by magmatic events, whereas the intensity of replacement dolomitization was controlled by host rock texture, varied bulk chemistry of host rock, circulating fluid and temperature.

Catalytic hydrolysis of sodium borohydride for hydrogen production using phosphorylated silica particles - Kottaikalai Ganesan; Chelvam Hayagreevan; Ramkumar Rahul; Arockiam John Jeevagan; Thambidurai Adinaveen; Durvas Seshian Bhuvaneshwari; Palanisamy Muthukumar; Murugan Amalraj (Environmental Science and Pollution Research, 2022)

Probing the thermo tolerant endosymbiont genus Durusdinium (Clade D) in the scleractinian corals of Palk Bay, Southeast coast of India - Murugesan Rajesh Kannan; Ramkumar Balakrishnan; Muneeswaran Thillaichidambaram; Sivakumar Natesan; Gunasekaran Paramasamy; Sanjeevi Prakash; Ramakritinan Chockalingam Muthiah (Biologia, 2022)

Simulated dynamics and thermodynamics processes leading to the rapid intensification of rare tropical cyclones over the North Indian Oceans - Arpita Munsi; Amit Kesarkar; Jyoti Bhate; Kasturi Singh; Abhishek Panchal; Govindan Kutty; Ramkumar Giri (Journal of Earth System Science, 2022)

Analysis of bluetongue disease epizootics in sheep of Andhra Pradesh, India using spatial and temporal autocorrelation - Ravichandran Karthikeyan; Ramkumar N Rupner; Shiva Reddy Koti; Nagaraj Jaganathasamy; Michael V. Lalrinzuala; Sachin Sharma; Shikha Tamta; Rotluangkimi; Sukdeb Nandi; Yashpal Singh Malik; Zunjar Baburao Dubal; Dharmendra Kumar Sinha; et al. (Veterinary Research Communications, 2022)

Biogenic synthesis of copper nanoparticles using Vitis vinifera L. seed extract, and its in-vitro biological applications - Janakiraman Vardhana; Ramarajan Sivasankaran; Thakku R. Ramkumar; Jeyachandran Anitha (Journal of Plant Biochemistry and Biotechnology, 2022)

Analysis of positive correlation in magnitude and time measurement for earthquake using electric signals - Oumaima Saidani; Ramkumar Raja Manoharan; Ahmed Samir Naje; Ruby Mishra; Arjun Subburaj; Maheswari S; Mohamed Yacin Sikkandar; Sankar Ganesh Sundaram; Regin Rajan; Sudhakar Sengan (Earth Science Informatics, 2022)

Genetic and epigenetic modes of the regulation of somatic embryogenesis: a review - Iyyakkannu Sivanesan; Safia Nayeem; Baskar Venkidasamy; Sree Preethy Kuppuraj; Chithraanjane RN; Ramkumar Samynathan (Biologia Futura, 2022)

Ropanicant (SUVN-911), an α4β2 nicotinic acetylcholine receptor antagonist intended for the treatment of depressive disorders: pharmacological, behavioral, and neurochemical characterization - Ramakrishna Nirogi; Renny Abraham; Pradeep Jayarajan; Venkatesh Goura; Rajesh Kallepalli; Rajesh babu Medapati; Jayaprakash Tadiparthi; Vinod kumar Goyal; Santosh kumar Pandey; Ramkumar Subramanian; Surendra Petlu; Jagadeesh Babu Thentu; et al. (Psychopharmacology, 2022)

Environmental pressure on estuary sediment texture and grain size in India versus other locations (China, South Korea, Uruguay, and Argentina) - Remy Rumuri; Thirunavukkarasu Ramkumar; Sivaprakasam Vasudevan; Gopalakrishnan Gnanachandrasamy (Arabian Journal of Geosciences, 2022)

A telephonic survey of health-related quality of life of outpatient department dropout Parkinson’s disease patients during the COVID-19 pandemic - Atul Goel; Sunil K. Narayan; Ramkumar Sugumaran (Acta Neurologica Belgica, 2022)

Genetic diversity analysis of wild and cultivated Rosa species of India using microsatellite markers and their comparison with morphology based diversity - Abhay Kumar Gaurav; Namita; D. V. S. Raju; M. K. Ramkumar; M. K. Singh; Bhupinder Singh; S. Gopala Krishnan; Sapna Panwar; Amitha Mithra Sevanthi (Journal of Plant Biochemistry and Biotechnology, 2022)

Particle-Size-Dependent Filtration Efficiency, Breathability, and Flow Resistance of Face Coverings and Common Household Fabrics Used for Face Masks During the COVID-19 Pandemic - Olukayode James Ayodeji; Terrell A. Hilliard; Seshadri Ramkumar (International Journal of Environmental Research, 2022)

Performance enhancement of solar photovoltaic (PV) module using a novel flat plate (NFP) glass cover by reducing the effect of bird dropping (BD) settlement - Anil Kumar Sisodia; Ramkumar Mathur (Environmental Science and Pollution Research, 2022)

Impact of computerised physician order entry (CPOE) on the incidence of chemotherapy-related medication errors: a systematic review - Suresh Kumar Srinivasamurthy; Ramkumar Ashokkumar; Sunitha Kodidela; Scott C. Howard; Caroline Flora Samer; Uppugunduri Satyanarayana Chakradhara Rao (European Journal of Clinical Pharmacology, 2021)
Purpose Computerised prescriber (or physician) order entry (CPOE) implementation is one of the strategies to reduce medication errors. The extent to which CPOE influences the incidence of chemotherapy-related medication errors (CMEs) was not previously collated and systematically reviewed. Hence, this study was designed to collect, collate, and systematically review studies to evaluate the effect of CPOE on the incidence of CMEs. Methods A search was performed of four databases from 1 January 1995 until 1 August 2019. English-language studies evaluating the effect of CPOE on CMEs were selected as per inclusion and exclusion criteria. The total CMEs normalised to total prescriptions pre- and post-CPOE were extracted and collated to perform a meta-analysis using the ‘meta’ package in R. The systematic review was registered with PROSPERO CRD42018104220. Results The database search identified 1621 studies. After screening, 19 studies were selected for full-text review, of which 11 studies fulfilled the selection criteria. The meta-analysis of eight studies with a random effects model showed a risk ratio of 0.19 (95% confidence interval: 0.08–0.44) favouring CPOE (I 2 = 99%). Conclusion The studies have shown consistent reduction in CMEs after CPOE implementation, except one study that showed an increase in CMEs. The random effects model in the meta-analysis of eight studies showed that CPOE implementation reduced CMEs by 81%.

Overview of miRNA biogenesis and applications in plants - Baniekal Hiremath Gangadhar; Baskar Venkidasamy; Ramkumar Samynathan; Balu Saranya; Ill-Min Chung; Muthu Thiruvengadam (Biologia, 2021)

An investigation on the assessment of mercury concentration and its spatial distribution in Kodaikanal Lake sediments, South India - Balamurugan Palani; Sivaprakasam Vasudevan; Thirunavukkarasu Ramkumar; Selvaganapathi Rajendiran (Arabian Journal of Geosciences, 2021)

Samelisant (SUVN-G3031), a potent, selective and orally active histamine H3 receptor inverse agonist for the potential treatment of narcolepsy: pharmacological and neurochemical characterisation - Ramakrishna Nirogi; Vijay Benade; Saivishal Daripelli; Ramkumar Subramanian; Venkatesh Kamuju; Gopinadh Bhyrapuneni; Nageswara Rao Muddana; Venkat Reddy Mekala; Surendra Petlu; Pradeep Jayarajan; Rajesh Badange; Anil Shinde; et al. (Psychopharmacology, 2021)

Simultaneous detection of medium-scale traveling ionospheric disturbances and ionospheric plasma irregularities over Srinagar, J&K, India - Aashiq Hussain Bhat; Bilal Ahmad Ganaie; T. K. Ramkumar; P. Pavan Chaitanya; Manzoor A. Malik (Acta Geophysica, 2021)

Lmo4 Deficiency Enhances Susceptibility to Cisplatin-Induced Cochlear Apoptosis and Hearing Loss - Rita Rosati; Monazza Shahab; Vickram Ramkumar; Samson Jamesdaniel (Molecular Neurobiology, 2021)

Neurodegenerative Implications of Neuronal Cytoplasmic Protein Dysfunction in Response to Environmental Contaminants - Odia Osemwegie; Seshadri Ramkumar; Ernest E. Smith (Neurotoxicity Research, 2021)

Allele mining for a drought responsive gene DRO1 determining root growth angle in donors of drought tolerance in rice (Oryza sativa L.) - Bablee Kumari Singh; M. K. Ramkumar; Monika Dalal; Archana Singh; Amolkumar U. Solanke; Nagendra K. Singh; Amitha Mithra Sevanthi (Physiology and Molecular Biology of Plants, 2021)

Effect of additives on the stability of ethanol-diesel blends for IC engine application - Ramkumar Shanmugam; Parthasarathy Murugesan; Gedisa Gudeta Guye; Boopathi Duraisamy (Environmental Science and Pollution Research, 2021)

Organopesticides and fertility: where does the link lead to? - Baskar Venkidasamy; Umadevi Subramanian; Ramkumar Samynathan; Govindasamy Rajakumar; Mohammad Ali Shariati; Ill-Min Chung; Muthu Thiruvengadam (Environmental Science and Pollution Research, 2021)

Investigation of performance enhancement of solar still incorporated with Gallus gallus domesticus cascara as sensible heat storage material - Gurukarthik Babu Balachandran; Prince Winston David; Gokul Rajendran; Mohamed Nasrulla Akbar Ali; Vignesh Radhakrishnan; Ramkumar Balamurugan; MuthuManokar Athikesavan; Ravishankar Sathyamurthy (Environmental Science and Pollution Research, 2021)

Sharpening gene editing toolbox in Arabidopsis for plants - Sagar S. Arya; Binod K. Mahto; Thakku R. Ramkumar; Sangram K. Lenka (Journal of Plant Biochemistry and Biotechnology, 2020)

Novel pathways of inflammation in human fetal membranes associated with preterm birth and preterm pre-labor rupture of the membranes - Ramkumar Menon; Faranak Behnia; Jossimara Polettini; Lauren S. Richardson (Seminars in Immunopathology, 2020)

Observed changes in extreme rain indices in semiarid and humid regions of Godavari basin, India: risks and opportunities - Aradhana Yaduvanshi; Ashwini Kulkarni; Ramkumar Bendapudi; Kaushik Haldar (Natural Hazards, 2020)

Planetary waves in the mesosphere lower thermosphere during stratospheric sudden warming: observations using a network of meteor radars from high to equatorial latitudes - N. Koushik; K. Kishore Kumar; Geetha Ramkumar; K. V. Subrahmanyam; G. Kishore Kumar; W. K. Hocking; Maosheng He; Ralph Latteck (Climate Dynamics, 2020)

Macrophage mediation in normal and diabetic wound healing responses - Goutham V. Ganesh; Kunka Mohanram Ramkumar (Inflammation Research, 2020)

Cross-sectional study on rotavirus A (RVA) infection and assessment of risk factors in pre- and post-weaning piglets in India - O. R. VinodhKumar; S. Sircar; B. S. Pruthvishree; K. R. Nirupama; B. R. Singh; D. K. Sinha; Ramkumar Rupner; A. Karthikeyan; R. Karthikeyan; Z. B. Dubal; Y. S. Malik (Tropical Animal Health and Production, 2020)

Assessing differential vulnerability of communities in the agrarian context in two districts of Maharashtra, India - Bhavana Rao Kuchimanchi; Divya Nazareth; Ramkumar Bendapudi; Suchita Awasthi; Marcella D’Souza (Climate and Development, 2019)

Characterization of internal inertia gravity wave over a low latitude: results from the RONAC-2012 campaign - K. N. Uma; Siddarth Shankar Das; K. Kishore Kumar; K. V. Subrahmanyam; G. Ramkumar (Meteorology and Atmospheric Physics, 2019)

Characterization of inertia gravity waves and associated dynamics in the lower stratosphere over the Indian Antarctic station, Bharati (69.4°S, 76.2°E) during austral summers - N. Koushik; Karanam Kishore Kumar; K. V. Subrahmanyam; Geetha Ramkumar; I. A. Girach; M. Santosh; K. Nalini; M. Nazeer; P. R. Shreedevi (Climate Dynamics, 2019)

Facies, depositional environments, and anatomy of the Subis build-up in Sarawak, Malaysia: implications on other Miocene isolated carbonate build-ups - Bing Bing Saw; Markus Schlaich; Michael C. Pöppelreiter; Mu. Ramkumar; Peter Lunt; Jose Antonio Gamez Vintaned; Syed Haroon Ali (Facies, 2019)

Smartphone geospatial apps for dengue control, prevention, prediction, and education: MOSapp, DISapp, and the mosquito perception index (MPI) - A. N. Babu; E. Niehaus; S. Shah; C. Unnithan; P. S. Ramkumar; J. Shah; V. V. Binoy; B. Soman; M. C. Arunan; C. P. Jose (Environmental Monitoring and Assessment, 2019)

Transport Analysis of Engineered Liver Tissue Fabricated Using a Capsule-Based, Modular Approach - Ramkumar T. Annamalai; Howard W. T. Matthew (Annals of Biomedical Engineering, 2019)

Morphological Deformities in Neotrygon kuhlii (Muller & Henle, 1841) from Gulf of Mannar, Bay of Bengal, India - L. Ranjith; R. Saravanan; C. Kalidas; M. Kavitha; S. Ramkumar; K. K. Joshi; P. P. Manojkumar (Thalassas: An International Journal of Marine Sciences, 2019)

Methamphetamine Induces Apoptosis of Microglia via the Intrinsic Mitochondrial-Dependent Pathway - Anna V. Sharikova; Elizabeth Quaye; Jun Yong Park; Maxwell C. Maloney; Habben Desta; Ramkumar Thiyagarajan; Kenneth L. Seldeen; Neil U. Parikh; Parteet Sandhu; Alexander Khmaladze; Bruce R. Troen; Stanley A. Schwartz; et al. (Journal of Neuroimmune Pharmacology, 2018)

Identifying hotspots in land use land cover change and the drivers in a semi-arid region of India - Vijayasekaran Duraisamy; Ramkumar Bendapudi; Ajit Jadhav (Environmental Monitoring and Assessment, 2018)

Simultaneous observations of the quasi 2-day wave climatology over the low and equatorial latitudes in the mesosphere lower thermosphere - Karanam Kishore Kumar; Kandula Venkata Subrahmanyam; Sneha Susan Mathew; N. Koushik; Geetha Ramkumar (Climate Dynamics, 2018)

RETRACTED ARTICLE: ROS-mediated cytotoxic activity of ZnO and CeO2 nanoparticles synthesized using the Rubia cordifolia L. leaf extract on MG-63 human osteosarcoma cell lines - Natarajan Sisubalan; Vijayan Sri Ramkumar; Arivalagan Pugazhendhi; Chandrasekaran Karthikeyan; Karuppusamy Indira; Kasi Gopinath; Abdulrahman Syedahamed Haja Hameed; Mohamed Hussain Ghouse Basha (Environmental Science and Pollution Research, 2018)

Biogenic synthesis of gold nanoparticles from Terminalia arjuna bark extract: assessment of safety aspects and neuroprotective potential via antioxidant, anticholinesterase, and antiamyloidogenic effects - Natarajan Suganthy; Vijayan Sri Ramkumar; Arivalagan Pugazhendhi; Giovanni Benelli; Govindaraju Archunan (Environmental Science and Pollution Research, 2018)

Searching of toxic metal pollution by using geospatial technology on the Kodaikanal Lake—near industrial area - Balamurugan Palani; Sivaprakasam Vasudevan; Thirunavukkarasu Ramkumar (Arabian Journal of Geosciences, 2017)

Identification of saline water intrusion in part of Cauvery deltaic region, Tamil Nadu, Southern India: using GIS and VES methods - G. Gnanachandrasamy; T. Ramkumar; S. Venkatramanan; S. Y. Chung; S. Vasudevan (Marine Geophysical Research, 2016)

Identification and validation of novel alleles of rice blast resistant gene Pi54, and analysis of their nucleotide diversity in landraces and wild Oryza species - G. Ramkumar; M. S. Madhav; S. J. S. Rama Devi; B. Umakanth; M. K. Pandey; M. S. Prasad; R. M. Sundaram; B. C. Viraktamath; V. Ravindra Babu (Euphytica, 2016)

Insecticidal potential of Ocimum canum plant extracts against Anopheles stephensi, Aedes aegypti and Culex quinquefasciatus larval and adult mosquitoes (Diptera: Culicidae) - Jimmantiyur Madhappan Murugan; Govindaraju Ramkumar; Muthugoundar Subramanian Shivakumar (Natural Product Research, 2016)

Influence of physicochemical and nutritional factors on bacterial diversity in mangrove sediments along the southwest coast of Tamilnadu, India - S. Prakash; R. Ramasubburayan; P. Iyapparaj; N. K. Ahila; V. Sri Ramkumar; A. Palavesam; G. Immanuel; E. Kannapiran (Environmental Monitoring and Assessment, 2015)

Environmental monitoring and assessment of heavy metals in surface sediments at Coleroon River Estuary in Tamil Nadu, India - S. Venkatramanan; S. Y. Chung; T. Ramkumar; S. Selvam (Environmental Monitoring and Assessment, 2015)

Comprehensive studies of hydrogeochemical processes and quality status of groundwater with tools of cluster, grouping analysis, and fuzzy set method using GIS platform: a case study of Dalcheon in Ulsan City, Korea - S. Venkatramanan; S. Y. Chung; R. Rajesh; S. Y. Lee; T. Ramkumar; M. V. Prasanna (Environmental Science and Pollution Research, 2015)

Influence of hydrogeochemical processes and assessment of suitability for groundwater uses in Busan City, Korea - S. Y. Chung; S. Venkatramanan; T. H. Kim; D. S. Kim; T. Ramkumar (Environment, Development and Sustainability, 2015)

Antigonon leptopus : a potent biological source for extermination of fish bacterial pathogens Providencia and Aeromonas - Govindasamy Balasubramani; Paramasivam Deepak; Rajamani Sowmiya; Rajendiran Ramkumar; Pachiappan Perumal (Natural Product Research, 2015)

Nucleotide variation and identification of novel blast resistance alleles of Pib by allele mining strategy - G. Ramkumar; M. S. Madhav; S. J. S. Rama Devi; M. S. Prasad; V. Ravindra Babu (Physiology and Molecular Biology of Plants, 2015)

Effect of orientation of transcription of a gene in an inverted transferred DNA repeat on transcriptional gene silencing in rice transgenics—a case study - Thakku R. Ramkumar; Chidambaram Parameswari; Thennavan Sugapriya; Karuppannan Veluthambi (Physiology and Molecular Biology of Plants, 2015)

An assessment of selected hydrochemical parameter trend of the Nakdong River water in South Korea, using time series analyses and PCA - S. Y. Chung; S. Venkatramanan; N. Park; R. Rajesh; T. Ramkumar; B. W. Kim (Environmental Monitoring and Assessment, 2015)

Identification and characterization of tsunami deposits off southeast coast of India from the 2004 Indian Ocean tsunami: Rock magnetic and geochemical approach - S Veerasingam; R Venkatachalapathy; N Basavaiah; T Ramkumar; S Venkatramanan; K Deenadayalan (Journal of Earth System Science, 2014)

A methodology for separating uncertainty and variability in the life cycle greenhouse gas emissions of coal-fueled power generation in the USA - Zoran J. N. Steinmann; Mara Hauck; Ramkumar Karuppiah; Ian J. Laurenzi; Mark A. J. Huijbregts (The International Journal of Life Cycle Assessment, 2014)

A spatially explicit data-driven approach to assess the effect of agricultural land occupation on species groups - Pieter M. F. Elshout; Rosalie van Zelm; Ramkumar Karuppiah; Ian J. Laurenzi; Mark A. J. Huijbregts (The International Journal of Life Cycle Assessment, 2014)

Effect of distal sugars and interglycosidic linkage on the N-glycoprotein linkage region conformation: synthesis and X-Ray crystallographic investigation of β-1-N-alkanamide derivatives of cellobiose and maltose as disaccharide analogs of the conserved chitobiosylasparagine linkage - Manoharan Mathiselvam; Venkatachalam Ramkumar; Duraikkannu Loganathan; Serge Pérez (Glycoconjugate Journal, 2014)

Heavy metal distribution in surface sediments of the Tirumalairajan river estuary and the surrounding coastal area, east coast of India - S. Venkatramanan; T. Ramkumar; I. Anithamary; S. Vasudevan (Arabian Journal of Geosciences, 2014)

Influence of light qualities on antifungal lipopeptide synthesis in Bacillus amyloliquefaciens JBC36 - Gandhimani Ramkumar; Sang-Mi Yu; Yong Hoon Lee (European Journal of Plant Pathology, 2013)

Speciation of selected heavy metals geochemistry in surface sediments from Tirumalairajan river estuary, east coast of India - S. Venkatramanan; T. Ramkumar; I. Anithamary; M. P. Jonathan (Environmental Monitoring and Assessment, 2013)

Morphological characteristics of Tirumalairajan river, East Coast of India—a GIS approach - Senapathi Venkatramanan; Thirunavukkarasu Ramkumar; Irudhayanathan Anithamary; Poovalinga Ganesh (Arabian Journal of Geosciences, 2013)

Distribution of grain size, clay mineralogy and organic matter of surface sediments from Tirumalairajanar Estuary, Tamilnadu, east coast of India - Senapathi Venkatramanan; Thirunavukkarasu Ramkumar; Irudhayanathan Anithamary (Arabian Journal of Geosciences, 2013)

Application of remote sensing and GIS analysis for identifying groundwater potential zone in parts of Kodaikanal Taluk, South India - Murugesan Bagyaraj; Thirunavukkarasu Ramkumar; Senapathi Venkatramanan; Balasubramanian Gurugnanam (Frontiers of Earth Science, 2013)

Investigation of genetic risk factors for chronic adult diseases for association with preterm birth - Nadia Falah; Jude McElroy; Victoria Snegovskikh; Charles J. Lockwood; Errol Norwitz; Jeffey C. Murray; Edward Kuczynski; Ramkumar Menon; Kari Teramo; Louis J. Muglia; Thomas Morgan (Human Genetics, 2013)

Evaluation of hydrogeochemical parameters and quality assessment of the groundwater in Kottur blocks, Tiruvarur district, Tamilnadu, India - Thirunavukkarasu Ramkumar; Senapathi Venkatramanan; Irudhayanathan Anithamary; Sheik Mohamed Syed Ibrahim (Arabian Journal of Geosciences, 2013)

Genetic structure and diversity of India hybrid tea - S. N. Raina; P. S. Ahuja; R. K. Sharma; S. C. Das; P. Bhardwaj; R. Negi; V. Sharma; S. S. Singh; R. K. Sud; R. K. Kalia; V. Pandey; J. Banik; et al. (Genetic Resources and Crop Evolution, 2012)

The molecular diversity and evolution of Rice tungro bacilliform virus from Indian perspective - Satendra K. Mangrauthia; P. Malathi; Surekha Agarwal; B. Sailaja; Jagrati Singh; G. Ramkumar; D. Krishnaveni; S. M. Balachandran (Virus Genes, 2012)

Variability of mesopause temperature derived from two independent methods using meteor radar and its comparison with SABER and EOS MLS and a collocated multi-wavelength dayglow photometer over an equatorial station, Thumba (8.5° N, 76.5° E) - Siddarth Shankar Das; Karanam Kishore Kumar; Subrata Kumar Das; Chandrasekharan Vineeth; Tarun Kumar Pant; Geetha Ramkumar (International Journal of Remote Sensing, 2012)

Genetic variation of coat protein gene among the isolates of Rice tungro spherical virus from tungro-endemic states of the India - Satendra K. Mangrauthia; P. Malathi; Surekha Agarwal; G. Ramkumar; D. Krishnaveni; C. N. Neeraja; M. Sheshu Madhav; D. Ladhalakshmi; S. M. Balachandran; B. C. Viraktamath (Virus Genes, 2012)

Persistence and Dissipation Kinetics of Deltamethrin on Chili in Different Agro-Climatic Zones of India - Suneet Pandher; S. K. Sahoo; R. S. Battu; Balwinder Singh; M. S. Saiyad; A. R. Patel; P. G. Shah; C. Narendra Reddy; D. Jagdishwar Reddy; K. Narasimha Reddy; Ch. Sreenivasa Rao; Tirthankar Banerjee; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Stable isotope analyses of belemnites from the Kachchh Basin, western India: paleoclimatic implications for the Middle to Late Jurassic transition - Matthias Alberti; Franz T. Fürsich; Dhirendra K. Pandey; Mu. Ramkumar (Facies, 2012)

Distribution and Accumulation of Metals in the Surface Sediments of Coleroon River Estuary, East Coast of India - Irudhayanathan Anithamary; Thirunavukkarasu Ramkumar; Senapathi Venkatramanan (Bulletin of Environmental Contamination and Toxicology, 2012)

Simultaneous observations of SAO and QBO in winds, temperature and ozone in the tropical middle atmosphere over Thumba (8.5°N, 77°E) - Karanam Kishore Kumar; Debadatta Swain; Sherine Rachel John; Geetha Ramkumar (Climate Dynamics, 2011)

Environmental magnetic and geochemical characteristics of Chennai coastal sediments, Bay of Bengal, India - R VENKATACHALAPATHY; S VEERASINGAM; N BASAVAIAH; T RAMKUMAR; K DEENADAYALAN (Journal of Earth System Science, 2011)

Inhibitory effect of Gymnema Montanum leaves on α-glucosidase activity and α-amylase activity and their relationship with polyphenolic content - Kunga Mohan Ramkumar; Balsamy Thayumanavan; Thayumanavan Palvannan; Palanisamy Rajaguru (Medicinal Chemistry Research, 2010)

Alterations in inheritance pattern and level of cytosine DNA methylation, and their relationship with heterosis in rice - K. Sakthivel; K. Girishkumar; G. Ramkumar; V. V. Shenoy; S. T. Kajjidoni; P. M. Salimath (Euphytica, 2010)

Petroleum Hydrocarbon Concentrations in Marine Sediments Along Chennai Coast, Bay of Bengal, India - R. Venkatachalapathy; S. Veerasingam; T. Ramkumar (Bulletin of Environmental Contamination and Toxicology, 2010)

A synthetic globotriaosylceramide analogue inhibits HIV-1 infection in vitro by two mechanisms - Amanda L. Harrison; Martin L. Olsson; R. Brad Jones; Stephanie Ramkumar; Darinka Sakac; Beth Binnington; Stephen Henry; Clifford A. Lingwood; Donald R. Branch (Glycoconjugate Journal, 2010)

Chiari II Malformation Mimicking Partial Rhombencephalosynapsis? A Case Report - Prasad Guntur Ramkumar; Avinash Kumar Kanodia; Ganapathy Ananthakrishnan; Richard Roberts (The Cerebellum, 2010)

87Sr/86Sr anomalies in Late Cretaceous-Early Tertiary strata of the Cauvery basin, south India: Constraints on nature and rate of environmental changes across K-T boundary - Mu Ramkumar; Doris Stüben; Zsolt Berner; Jens Schneider (Journal of Earth System Science, 2010)

Genetic characterization of 2006–2008 isolates of Chikungunya virus from Kerala, South India, by whole genome sequence analysis - E. Sreekumar; Aneesh Issac; Sajith Nair; Ramkumar Hariharan; M. B. Janki; D. S. Arathy; R. Regu; Thomas Mathew; M. Anoop; K. P. Niyas; M. R. Pillai (Virus Genes, 2010)

Antidiabetic effects of scoparic acid D isolated from Scoparia dulcis in rats with streptozotocin-induced diabetes - Muniappan Latha; Leelavinothan Pari; Kunga Mohan Ramkumar; Palanisamy Rajaguru; Thangaraj Suresh; Thangavel Dhanabal; Sandhya Sitasawad; Ramesh Bhonde (Natural Product Research, 2009)

Genetic regulation of amniotic fluid TNF-alpha and soluble TNF receptor concentrations affected by race and preterm birth - Ramkumar Menon; Digna R. Velez; Nicole Morgan; Salvatore J. Lombardi; Stephen J. Fortunato; Scott M. Williams (Human Genetics, 2008)

A gene-trap strategy identifies quiescence-induced genes in synchronized myoblasts - Ramkumar Sambasivan; Grace K. Pavlath; Jyotsna Dhawan (Journal of Biosciences, 2008)

Development of a DNA marker for distinguishing CMS lines from fertile lines in rice (Oryza sativa L.) - Nirmala Rajendran; Ramkumar Gandhimani; Sukhpal Singh; Kadirvel Palchamy (Euphytica, 2007)

Restorative Effect of Kalpaamruthaa, an Indigenous Preparation, on Oxidative Damage in Mammary Gland Mitochondrial Fraction in Experimental Mammary Carcinoma - Shanmugam Arulkumaran; Vanu Ramkumar Ramprasath; Palanivelu Shanthi; Panchanatham Sachdanandam (Molecular and Cellular Biochemistry, 2006)

Announcement - Mu. Ramkumar (Journal of the Indian Society of Remote Sensing, 2006)

Influence of spacing on growth and yield of sugarcane raised throughin vitro micropropagation - S. Raghu; S. Jayaram; S. Ramkumar; P. Prabakaran; V. Vekatesalu (Sugar Tech, 2006)

Tolerance of Bt corn (MON 810) to maize stem borer, Chilo partellus (Lepidoptera: Pyralidae) - Ramkumar; K. C. Ravi; Farah Deeba; J. N. Nandi; K. S. Mohan; T. M. Manjunath (Plant Cell Reports, 2005)

Semecarpus anacardium Linn. nut milk extract, an indigenous drug preparation, modulates reactive oxygen/nitrogen species levels and antioxidative system in adjuvant arthritic rats - Vanu Ramkumar Ramprasath; Palanivelu Shanthi; Panchanatham Sachdanandam (Molecular and Cellular Biochemistry, 2005)

Barium anomaly preceding K/T boundary: possible causes and implications on end Cretaceous events of K/T sections in Cauvery basin (India), Israel, NE-Mexico and Guatemala - M. Ramkumar; M. Harting; D. Stüben (International Journal of Earth Sciences, 2005)

Cell cycle of Chlorella vulgaris can deviate from the synchronous binary division model - Ramkumar K. Mandalam; Bernhard Ø. Palsson (Biotechnology Letters, 1997)